An evaluation of the technical viability of employing combinations of xanthan gum and clay as an additive in Tunnel Boring Machine (TBM) slurries - Lee, Sojeong; Titulaer, Barrie; Ryu, Hee Hwan; Chang, Ilhan (Geomechanics and Engineering, 2024)
The issue of problematic disposal of excavated material, commonly referred to as muck, generated during tunnel boring machine (TBM) excavation has emerged as an environmental challenge amidst the escalating demand for sustainable engineering solutions. TBM excavation operations necessitate the use of a slurry to bolster the excavation process and aid in muck conveyance. Typically composed of bentonite, this TBM slurry is conventionally discarded along with the excavated spoils, posing risks to human safety and raising environmental contamination apprehensions. This study aims to explore a novel slurry material as a means to mitigate the toxicity associated with muck disposal. Given the notable adsorption capabilities of bentonite, alternative options such as kaolinite clay and xanthan gum biopolymer are under consideration. Through experimental analysis, various combinations of bentonite clay, kaolinite clay, and xanthan gum are examined to assess their effectiveness in enhancing tunneling performance and optimizing transport properties. The evaluated parameters encompass rheological characteristics, swelling behavior, permeability, suspended viscosity and stickiness. Employing statistical analysis integrated with random weighting factors and the measured properties of each slurry candidate, competitiveness of each slurry candidate is analyzed. The findings of this investigation, accounting for 47.31% priority across all probabilistic scenarios, indicate that a specific blend consisting of bentonite and xanthan gum (2.5% bentonite, 0.75% xanthan gum) demonstrates considerable promise as a substitute for conventional bentonite-based slurries (7.5% bentonite) in TBM excavation applications.
Keywords: Biopolymer-based soil treatment; Engineering solutions; Environmental challenges; Excavated materials; Geotechnical; Kaolinite clay; Soil treatments; Sustainable engineering; Technical viability; Tunnel boring; biopolymer; biopolymer-based soil treatment (BPST); geotechnical engineering; slurry; xanthan gum